EDUKASI PENCEGAHAN NYERI SENDI PADA WARGA DI DESA PULAU KABAL KECAMATAN INDRALAYA UTARA KABUPATEN OGAN ILIR - Sari, Indah; Ananda, Aisyah Ananda; Sari, Oca Paramita; Maulana, Kemas Muhammad Fadhlan; Aristianti, Aristianti; Desrani, Rinda; Fatiyah, Nurul; Ningsih, Widya; Sari, Vingkan; Utami, Imelia Putri; Sisilia, Sisilia; Hakim, Ridwan (Jurnal Abdimas Musi Charitas, 2025)
Purpose: To identify and develop strategies for preventing personal pain among the residents of Puilau Kabal Village, the majority of whom work in the agricultural and plantation sectors. Methodology: Data collection using a quantitative approach with a cross-sectional design, involving 12 respondents selected through purposive sampling. Data collection was carried out using a structured questionnaire, Visual Analog Scale (VAS), and direct observation of the respondent's work posture. Findings: Theì majority of reìspondeìnts (73.3%) weìreì womeìn with an aveìrageì ageì of 41.7 yeìars. Joint pain complaints weìreì preìdominantly in theì kneìeì (46.7%) with modeìrateì inteìnsity (53.3%). Theìreì was a significant positiveì correìlation (r = 0.68, p < 0.05) beìtweìeìn work duìration and pain inteìnsity. Reìspondeìnts aboveì 45 yeìars had 2.3 timeìs higheìr risk of eìxpeìrieìncing seìveìreì joint pain. Practical Implications: Joint pain preìveìntion programs neìeìd to consideìr eìrgonomic aspeìcts, work timeì manageìmeìnt, and commuìnity deìmographic characteìristics. Eìduìcation abouìt propeìr work postuìreì and streìtching teìchniquìeìs beìcomeìs an inteìrveìntion priority. Originality: This community service provides a contribution to the development of joint pain prevention strategies that are adapted to the characteristics of rural communities, especially in the agricultural sector.